Next generation sequencing in nonsyndromic intellectual disability: from a negative molecular karyotype to a possible causative mutation detection. - Athanasakis, Emmanouil; Licastro, Danilo; Faletra, Flavio; Fabretto, Antonella; Dipresa, Savina; Vozzi, Diego; Morgan, Anna; d'Adamo, Adamo P; Pecile, Vanna; Biarnés, Xevi; Gasparini, Paolo (Am J Med Genet A, 2014)
The identification of causes underlying intellectual disability (ID) is one of the most demanding challenges for clinical Geneticists and Researchers. Despite molecular diagnostics improvements, the vast majority of patients still remain without genetic diagnosis. Here, we report the results obtained using Whole Exome and Target Sequencing on nine patients affected by isolated ID without pathological copy number variations, which were accurately selected from an initial cohort of 236 patients. Three patterns of inheritance were used to search for: (1) de novo, (2) X-linked, and (3) autosomal recessive variants. In three of the nine proband-parent trios analyzed, we identified and validated two de novo and one X-linked potentially causative mutations located in three ID-related genes. We proposed three genes as ID candidate, carrying one de novo and three X-linked mutations. Overall, this systematic proband-parent trio approach using next generation sequencing could explain a consistent percentage of patients with isolated ID, thus increasing our knowledge on the molecular bases of this disease and opening new perspectives for a better diagnosis, counseling, and treatment.
Keywords: Computational Biology; Exome; Female; Genes, Recessive; Genes, X-Linked; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Intellectual Disability; Karyotype; Male; Mutation; Workflow